USABILITY IN THE RECOVERY OF INFORMATION IN BIBLIOGRAPHICAL CATALOGS: evaluation of the online catalog of SIGAA from the perspective of UFRN graduate students - Brito e Silva, Mayane Paulino de; Vechiato, Fernando Luiz [UNESP] (Univ Federal Campina Grande, 2017)
It presents the results of an undergraduate research about usability in the context of bibliographic catalogs, namely in the online catalog of the Integrated System of Management of Academic Activities (SIGAA), having as a sample the postgraduate students of the Federal University of Rio Grande do Norte (UFRN). It aims to collaborate to improve the quality of the interaction of graduate students of UFRN with the online catalog of SIGAA. It uses as theoretical subsidy for conducting the research, exploratory and descriptive, books, periodicals, national and international databases, information science and related sites etc. It systematizes the data collection based on a methodological triangulation: heuristic evaluation of the SIGAA catalog, usability test and interview with the users. It points out the strengths and weaknesses of the catalog studied according to each step of the methodological triangulation, listing suggestions for improvements to the usability of the system. It concludes that UFRN graduate students are generally able to retrieve the documents represented in the SIGAA catalog, so that the interaction process with the catalog goes through some difficulties, but it occurs efficiently in the larger Part of the cases.
Keywords: Usability; Information Retrieval; Information Behavior; Online Catalog; Methodological Triangulation